Kajian penerapan kearifan lokal Kaombono Tai di Desa Kondowa Kecamatan Pasarwajo Kabupaten Buton - Filda, Filda; Rosmawati; Piliana, Wa Ode; Patiung, Seventry Meliana (Universitas Halu Oleo, 2025)
This research aims to determine the form and application of local wisdom Kaombono Tai in Kondowa Village, Pasarwajo District, Buton Regency. Data collection methods by observation, questionnaires, documentation, literature studies and ethnographic studies. The data analysis used is qualitative descriptive analysis with an ethnographic study approach. The determination of respondents was carried out purposively with seven respondents, namely three traditional leaders: Parabela (traditional leader), waci, imam; one Kondowa Village Head and three communities. Interviews were conducted directly with respondents regarding the form and application of local wisdom kaombono tai. Local wisdom is applied to all communities where it is prohibited to catch marine biota outside of the time of fishing and is prohibited from damaging the marine environment. Meanwhile, the form of local wisdom contains values, customary law, beliefs, sanctions and kabaria traditions (kaombo opening). The results of this research show that collaboration between the government and traditional institutions is very helpful in the effective application of local wisdom Kaombono Tai.